IMPLEMENTASI SISTEM INFORMASI DATA PELAKU USAHA PERIKANAN BUDIDAYA PADA DINAS PERIKANAN KOTA KUPANG - Frensile Susanti Ndoen; Meiton Boru; Clarissa E. A. Pah (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2023)
In 2022, the number of aquaculture business actors in the Kupang City Fisheries Service are 649 people, divided into 55 groups of business actors with 566 members and 83 individual business actors. Data processing for aquaculture business actors operated through Microsoft Office Excel (Ms. Excel) is not optimal because several obstacles frequently encountered, namely duplication of data, difficulty calculating the number of business actors, Large amounts of data are difficult to summarize because they are scattered across multiple Excel files, making it difficult for officers to create data reports on aquaculture business actors. Therefore, this study aims to create a system to assist officers in managing data on aquaculture business actors. The method used in this research is the Waterfall method because the advantage is that the quality of the resulting system will be good. After all, the implementation is carried out in stages. This system generates group data reports, business actor data, business data, pond data, production data, business registration data, training data, and histograms of the number of business actors based on gender, the number of businesses receiving Business Cards for Marine and Fisheries (KUSUKA), the number of businesses per nameplate group, the number of business actors per district, the number of businesses per district and the summary score of the number of aquaculture business actors. The results of black box testing conducted by three respondents to 12 menus show that all functional systems function as expected.